ANALISA SECURITY ACCESS SYSTEM DI AREA GEDUNG TOWER BANDAR UDARA TAMBOLAKA - Rifta Hasim Oktaviani; Fatmawati; Yuni Saptandari (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Tambolaka Airport was established in 1982, has a runway length of 1600 meters and was extended to 2300 meters in 20015. Tambolaka Airport has an Aerodrome Flight Information Service unit which is tasked with serving Air Traffic Guidance with the aim of preventing collisions between aircraft and aircraft or obstacles in the movement area. and maintain the safety, order and efficiency of air traffic. The establishment of security and safety in the world of aviation that is effective and efficient is something that is mandatory and indispensable in an effort to provide safe, fast and regular flight traffic services, a standardized security system is needed that aims to support flight safety. Many factors of air traffic services that can affect flight safety, these factors come from human resources and equipment that are arranged in such a way as possible with established standards in order to create safe, fast, and orderly traffic services. Writing this final project aims as one of the graduation requirements for cadets of the Diploma 3 Aviation Communication Study Program in order to obtain an Associate Expert (A.Md) degree, as a means to increase knowledge/insight for cadets at the Surabaya Aviation Polytechnic, readers and subsequent researchers, as one of the input material so that cadets are able to apply all theoretical knowledge received during class and laboratory education for 6 semesters. In this study, the data writing method uses gap analysis, which is to determine what steps need to be taken to move from the current state to the desired state or the desired future state. The research method that the author uses is using data collection methods: observation, documentation, and literature study.